Stimulating Sustainable Food Choices Using Virtual Reality: Taking an Environmental vs Health Communication Perspective on Enhancing Response Efficacy Beliefs. Issue 1 (2nd January 2022) - Meijers, Marijn H. C.; Smit, Eline S.; de Wildt, Kelly; Karvonen, Sonja-Greetta; van der Plas, Demi; van der Laan, L. Nynke
ABSTRACT: Personal response efficacy beliefs are vital in instigating, maintaining, and catalyzing environmental behavior change. In this experimental study ( N = 249), we investigated whether such efficacy beliefs could be stimulated using Virtual Reality. In a VR-supermarket, participants would see interactive pop-ups displaying impact messages when they picked up products, these are messages that display the (environmental or health) impact of a product. Our results show that these impact messages are effective in stimulating personal response efficacy beliefs and subsequently pro-environmental food choices. The heightened personal response efficacy beliefs positively affected maintaining and catalyzing behavior change (i.e. positive spill-over) up to two weeks after the VR-experience. The effectiveness of the impact messages did not depend on appeal type (health vs environmental appeal) or modality (text + visual vs text only) of the message. Theoretical and practical implications are discussed.